1988
DOI: 10.1136/jnnp.51.8.1078
|View full text |Cite
|
Sign up to set email alerts
|

Decreased glutamate dehydrogenase protein in spinocerebellar degeneration.

Abstract: SUMMARY A radioimmunoassay system for determining content of glutamate dehydrogenase (GDH) in human leukocytes was established and studied in 14 patients with spinocerebellar ataxia or atypical Parkinsonism. The protein content of leukocyte GDH was decreased in four patients and the reduction in the protein content was proportional to that in the enzyme activity. The ratio of GDH activity to protein content was invariable in healthy controls, diseased controls and patients with reduced GDH activity. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
4
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
4
4
0
1
Order By: Relevance
“…These differences are consistent with the electrophoretic characteristics of GDH isozymes purified from human brain [22]. Previous studies showed that GDH activities were differentially altered in neurologic patients [33–38], thus suggesting that these activities are under different genetic control. Since electroretinographic abnormalities have been detected in patients with spinocerebellar ataxia who have a selective deficiency of the heat‐labile GDH [2,38], studies on the molecular basis for the different thermal stability of the GDH isozymes may thus be of importance for understanding the biology of the human nervous systems and the genetic analysis of X‐linked neurodegeneration.…”
Section: Resultssupporting
confidence: 85%
“…These differences are consistent with the electrophoretic characteristics of GDH isozymes purified from human brain [22]. Previous studies showed that GDH activities were differentially altered in neurologic patients [33–38], thus suggesting that these activities are under different genetic control. Since electroretinographic abnormalities have been detected in patients with spinocerebellar ataxia who have a selective deficiency of the heat‐labile GDH [2,38], studies on the molecular basis for the different thermal stability of the GDH isozymes may thus be of importance for understanding the biology of the human nervous systems and the genetic analysis of X‐linked neurodegeneration.…”
Section: Resultssupporting
confidence: 85%
“…Our work with neurologic patients led to the finding that GDH is present in human tissues in "heat-labile" and "heat-stable" forms and that, in these patients, reduction in GDH activity was largely limited to the heat-labile component (Plaitakis et al, 1984). Similar results have been obtained by other (Konagaya et al, 1986;Kajiyama et al, 1988;Iwattsuji et al, 1989;Abe et al, 1992) but not all (Aubby et al, 1988;Duvoisin et al, 1988) investigators. Additional studies in our laboratory (Colon et al, 1986) showed the presence of two GDH activities in rat brain differing in their relative resistance to thermal inactivation, detergent extractability, and allosteric regulation characteristics.…”
supporting
confidence: 78%
“…Previous studies showed that GDH activities were differentially altered in neurologic patients (29,30), thus suggesting that these activities are under different genetic control. Because electroretinographic abnormalities have been detected in patients with spinocerebellar ataxia who have a selective deficiency of the heat-labile GDH isozymes (10,(31)(32)(33)(34), studies on the molecular basis for the different molecular properties of the GDH isozymes may, thus, be of importance for understanding the biology of the human nervous systems and the genetic analysis of X-linked neurodegeneration. Previously, two types of mitochondrial glutamate carrier (GC1 and GC2) were identified differing in their V max and K m values and in their tissue distribution (35).…”
Section: Discussionmentioning
confidence: 99%